2021
DOI: 10.1038/s41598-021-89929-3
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of schistosomula crude antigen (SCA) as a diagnostic tool for Schistosoma mansoni in low endemic human population

Abstract: The study aimed to determine the potential of schistosomula crude antigen (SCA) as a diagnostic target for anti-S. mansoni antibody detection. Cercariae were transformed into schistosomula, homogenized through sonication, and then centrifuged to obtain the SCA. SCA was evaluated using ELISA and dot blots immunoassays on 30 S. mansoni infected sera samples obtained from chronic patients and 30 non-infected humans’ sera samples. Either Kato-Katz or saline gradient method or both were employed as the diagnostic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 22 publications
0
2
0
1
Order By: Relevance
“…On the other side, the biomarker used as the diagnostic tool in the non-endemic regions is schistosomula crude antigen (SCA), which serves as a method for the detection of antibodies for Schistosoma mansoni. The aforementioned method has revealed promising results as compared with ELISAs and dot blots immunoassays [12]. The study performed on Belgian travellers also showed and confirmed that testing against Schistosoma antibodies and circulating anodic antigen (CAA) is helpful in the early detection of acute schistosomiasis [13].…”
Section: Discussionmentioning
confidence: 81%
“…On the other side, the biomarker used as the diagnostic tool in the non-endemic regions is schistosomula crude antigen (SCA), which serves as a method for the detection of antibodies for Schistosoma mansoni. The aforementioned method has revealed promising results as compared with ELISAs and dot blots immunoassays [12]. The study performed on Belgian travellers also showed and confirmed that testing against Schistosoma antibodies and circulating anodic antigen (CAA) is helpful in the early detection of acute schistosomiasis [13].…”
Section: Discussionmentioning
confidence: 81%
“…Довольно много исследований проводится с целью поиска новых мишеней для диагностики и дифференцировки различных инвазий, поисков новых антигенов и их комбинации [10,15,18,24,33,65,[77][78][79][80][81][82][83][84]. В качестве новых маркеров исследуют: сапозин-подобный белок [37], микроРНК, выделенные из экстравезикул сыворотки [85,86], катепсин L3 при шистосомозе [87], очищенный антиген паразита молекулярной массой 27 при фасцилезе [14], межгенный спейсерный участок ДНК F. hepatica [17], антиген шистосомул при инвазии S. mansoni [88]. Чувствительность методов на основе ПЦР зависит от количества копий гена, количества яиц паразита, качества ДНК и ингибиторов ПЦР в образце.…”
Section: молекулярно-генетические методыunclassified
“…These tests are, in general, well suited for areas with low transmission and can be rapid tests for travelers returning from endemic areas ( 119 , 120 ). Most antibody assays report on immunoglobulin G (IgG), and rarely immunoglobulin M (IgM) ( 121 , 122 ), that target crude antigen extracts like cercarial secretions, schistosome egg antigen (SEA), soluble adult worm antigen preparation (SWAP), or can be constructed to detect purified or recombinant antigens ( 106 , 123 , 124 ). Soon after exposure, patients present with an acute inflammatory response driven by the body’s immune response to schistosomula migration ( 125 ) and a positive antibody test is commonly the earliest diagnostic laboratory result.…”
Section: Diagnosis Of Schistosoma Species Infectionsmentioning
confidence: 99%